Effect of warm-ups involving static or dynamic stretching on agility, sprinting, and jumping performance in trained individuals - Chaouachi, A.; Castagna, C.; Chtara, M.; Brughelli, M.; Turki, O.; Galy, O.; Chamari, K.; Behm, D. G. (The Journal of Strength and Conditioning Research, 2010)
The objective of the present study was to investigate the effects of static and dynamic stretching alone and in combination on subsequent agility, sprinting, and jump performance. Eight different stretching protocols: (a) static stretch (SS) to point of discomfort (POD); (b) SS less than POD (SS<POD); (c) dynamic stretching (DS); (d) SS POD combined with DS (SS POD + DS); (v) SS<POD combined with DS (SS<POD + DS); (vi) DS combined with SS POD (DS + SS POD); (vii) DS combined with SS<POD (DS + SS<POD); and (viii) a control warm-up condition without stretching were implemented with a prior aerobic warm-up and followed by dynamic activities. Dependent variables included a 30-m sprint, agility run, and jump tests. The control condition (4.2 ± 0.15 seconds) showed significant differences (p = 0.05) for faster times than the DS + SS<POD (4.28s ± 0.17) condition in the 30-m (1.9%) sprint. There were no other significant differences. The lack of stretch-induced impairments may be attributed to the trained state of the participants or the amount of time used after stretching before the performance. Participants were either professional or national level elite athletes who trained 6-8 times a week with each session lasting ~90 minutes. Based on these findings and the literature, trained individuals who wish to implement static stretching should include an adequate warm-up and dynamic sport-specific activities with at least 5 or more minutes of recovery before their sport activity.